A quasi-experimental study of augmented reality athletics learning on motor skills and motivation in elementary students - Yan Indra Siregar; Fredrik Alfrets Makadada; Fadli Ihsan (Indonesian Institute For Counseling, Education and Therapy, 2026)
Fundamental movement skills (FMS) and learning motivation are essential for children’s physical development and participation in physical activity. However, many elementary school students demonstrate low motor competence and limited engagement in physical education due to conventional instructional approaches that are often repetitive and less interactive. Augmented Reality (AR) technology has emerged as a promising tool to enhance learning experiences and increase student motivation. Therefore, this study aimed to examine the effects of AR-based athletics learning on FMS and learning motivation among elementary school students. A quasi-experimental pretest–posttest control group design was employed involving 60 students aged 9–11 years. Participants were assigned to either an experimental group receiving AR-based athletics instruction or a control group receiving conventional instruction. The intervention was conducted over eight weeks. FMS were assessed using the Test of Gross Motor Development-3 (TGMD-3), while learning motivation was measured using a validated questionnaire. Data were analyzed using paired-sample and independent-sample t-tests and Cohen’s d effect size analysis. The results showed significant improvements in both FMS and motivation among students in the experimental group. FMS scores increased from 61.47 ± 6.28 to 78.53 ± 5.91, while motivation scores increased from 63.84 ± 5.74 to 82.15 ± 5.38 (p < 0.001). Large effect sizes were observed for FMS (d = 1.42) and motivation (d = 1.58). These findings indicate that AR-based athletics learning is an effective and innovative strategy for improving motor skills and learning motivation in physical education.